2011
DOI: 10.1042/cbi20100326
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mesenchymal stem cell from human umbilical cord tissue using a combination enzymatic and mechanical disassociation method

Abstract: MSCs (mesenchymal stem cells) promise a great potential for regenerative medicine due to their unique properties of self-renewal, high plasticity, modulation of immune response and the flexibility for genetic modification. Therefore, the increasing demand for cellular therapy necessitates a larger-scale production of MSC; however, the technical and ethical issues had put a halt on it. To date, studies have shown that MSC could be derived from human UC (umbilical cord), which is once considered as clinical wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 26 publications
3
57
2
1
Order By: Relevance
“…It gave us an yield of 1.5*10 5 ± 0.5*10 5 cells/8cm of UC after 12 days of processing ( Figure 1). These numbers were relatively low when compared to reports from other groups [17,35] and may be due to the variation in the initial quantity of the cord tissue used.…”
contrasting
confidence: 40%
“…It gave us an yield of 1.5*10 5 ± 0.5*10 5 cells/8cm of UC after 12 days of processing ( Figure 1). These numbers were relatively low when compared to reports from other groups [17,35] and may be due to the variation in the initial quantity of the cord tissue used.…”
contrasting
confidence: 40%
“…Furthermore, Sox2 is also involved in the maintenance of self-renewal of the osteoblastic lineage [31]. Recently, it was shown that mesenchymal stem cells derived from human umbilical cord constitutively express SOX2 and are capable of differentiating into osteoblast as well as adipocytes, indicating the involvement of SOX2 in osteoblast differentiation [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the tissue explant method has low separation efficiency, and the enzyme digestion method has many varying protocols, none of which are stable and efficient. In this study, we have compared the conventional tissue explant method (Ma et al 2005;Qiao et al 2008), the conventional enzyme digestion method (Wang et al 2004;Seshareddy et al 2008;Tong et al 2011) and a modified enzyme Fig. 4 Identification of cell antigen markers of the thirdgeneration of hUCMSCs isolated by the modified enzyme digestion method (9100).…”
Section: Discussionmentioning
confidence: 99%